The Effectiveness of the Management Information System in Improving the Quality of Education at SMP Negeri 1 Tumpaan, South Minahasa Regency - Mandei, Jul Merry; Siang, Jhoni Lagun; Mamahit, Meyke M. (Peneliti.net, 2025)
This study aims to identify and analyze: (1) the effectiveness of a management information system in improving the quality of education at SMP Negeri 1 Tumpaan, Minahasa Selatan Regency; (2) the supporting factors that enhance the use of the system for improving educational quality; (3) the inhibiting factors that constrain its use; and (4) the contribution of the system to advancing educational quality at the school. The research employs a qualitative method using a descriptive approach. Data collection techniques include interviews, observations, and document analysis conducted at SMP Negeri 1 Tumpaan. The findings reveal that: (1) SIM Dapodik plays a central role in education planning, class group (rombel) distribution, teacher task allocation, BOS fund management, and the implementation of quality improvement programs based on the Education Report Card; (2) the main supporting factors include operator competence, leadership support from the principal, adequate digital infrastructure, and technical training; (3) usage obstacles include unstable network access, lack of initial training, and delays in data collection from internal stakeholders; (4) the contribution of SIM Dapodik is evident in the school accreditation process _ even though it has not yet significantly impacted accreditation scores, the data stored in the system is essential for assessor verification and institutional validation. The system also encourages parental participation in updating student data and fosters effective communication between school and home. Dapodik’s data management is executed systematically and with care by the school operator, with password access kept confidential and records archived both manually and digitally. These practices have resulted in no reported concerns from teachers or parents regarding data leakage, indicating a high level of user trust. Overall, SIM Dapodik serves as a strategic instrument in data-driven educational governance oriented toward continuous quality improvement.